Determinants of Taxpayer Compliance in Indonesia's Integrated Identification System: Literacy, Socialization, Digital Services, and Security - Silvana Renjani Fitri; Annathasia Puji Erasashanti (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
ABSTRACT Purpose – This paper seeks to examine the factors influencing MSME taxpayer compliance during the transitional era of National Identity Number (NIK) and Taxpayer Identification Number (NPWP) integration. Specifically, it analyzes the roles of tax literacy, personal data security, digital service quality, and tax socialization in shaping compliance among small business owners. Methodology/approach – A quantitative approach was employed, collecting primary data through surveys. The sample consisted of 200 MSME entrepreneurs operating in the DKI Jakarta region, predominantly dominated by young, female digital-native entrepreneurs within the food and beverage sector. The collected data were analyzed using structural equation modeling via SmartPLS 4 to test the proposed hypotheses. Findings – It was found that all four proposed factors significantly and positively predict MSME taxpayer compliance. Personal data security emerged as the strongest predictor (Original Sample = 0.253, P = 0.002), followed by tax socialization (0.198, P = 0.045), tax literacy (0.193,P = 0.007), and digital service quality (0.134, P = 0.042). The results underscore that guaranteeing cybersecurity and simplifying digital tax systems are vital to fostering voluntary compliance during regulatory transitions. Novelty/value – As Indonesia undergoes a major structural shift toward a unified identity system (NIK-NPWP), this study offers timely empirical insights into how structural data security concerns and digital infrastructure readiness directly dictate compliance behavior among micro and small enterprises. Keywords: Taxpayer compliance, Literacy, NIK-NPWP integration, Personal data security, Digital tax service.